Barbed Voices : Oral History, Resistance, and the World War II Japanese American Social Disaster - Hansen, Arthur A. (Book collections on Project MUSE., 2018)
"An updated and annotated anthology of published articles written by a respected historian of Japanese American history. Featuring selected inmates and camp groups who spearheaded resistance movements in the ten War Relocation Authority-administered compounds. Provides an understanding how some of the 120,000 incarcerated Japanese Americans opposed threats"--Provided by publisher